Reframing Female Genital Cosmetic and Aesthetic Surgery: Ethics, Function, and Sexual Health Beyond Appearance - Mochamad Rizkar Arev Sukarsa (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
In recent years, the convergence of aesthetic medicine and urogynecology has reshaped the dialogue on women’s health. Procedures once confined to reconstructive domains—repairing pelvic floor disorders, perineal trauma, or postpartum laxity—now coexist with aesthetic motivations emphasizing appearance and self-confidence. This editorial reflects on how female genital cosmetic surgery (FGCS) and female genital aesthetic surgery (FGAS) overlap yet differ ethically, functionally, and philosophically.Defining FGCS and FGASAccording to the American College of Obstetricians and Gynecologists (ACOG) and the Royal College of Obstetricians and Gynaecologists (RCOG), FGCS comprises elective surgical procedures that modify the appearance of genitalia without clear medical indication. These interventions originate in the cosmetic surgery paradigm, focusing on visual symmetry and patient satisfaction. In contrast, FGAS has evolved within gynecology and minimally invasive aesthetic medicine, aiming not only at external appearance but also at comfort, tissue quality, and functional harmony. The distinction matters: while FGCS is largely appearance-driven, FGAS aspires toward holistic well-being and sexual confidence. Recognizing these nuances helps physicians maintain ethical boundaries and ensure that patient motivation is grounded in informed understanding rather than social pressure.